2015
DOI: 10.1159/000437308
|View full text |Cite
|
Sign up to set email alerts
|

Isolated Conjunctival Inflammation Suggestive of IgG4-Related Disease

Abstract: Purpose: In this interventional case report, we present the correlation between an isolated conjunctival inflammatory lesion and IgG4-related disease. Results: A 29-year-old female presented with a solitary conjunctival mass of the right eye. The rest of the ocular examination including orbital assessment was negative. Excisional biopsy was suggestive of IgG4-related disease. The patient was treated with oral steroids and remained disease free at 18 months of follow-up. Conclusions: Isolated conjunctival infla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…IgG4-ROD mainly involves the lacrimal gland, extraocular muscles and trigeminal nerve; the optic nerve, conjunctiva, sclera, uvea, and choroid are rarely involved [4][5][6][7][8]. Despite the rarity of conjunctival involvement in IgG4-ROD [6][7][8], this paper reports a another very rare case of LC with strong positive expression of IgG4 in histopathological results with only one published case in literature.…”
mentioning
confidence: 79%
See 1 more Smart Citation
“…IgG4-ROD mainly involves the lacrimal gland, extraocular muscles and trigeminal nerve; the optic nerve, conjunctiva, sclera, uvea, and choroid are rarely involved [4][5][6][7][8]. Despite the rarity of conjunctival involvement in IgG4-ROD [6][7][8], this paper reports a another very rare case of LC with strong positive expression of IgG4 in histopathological results with only one published case in literature.…”
mentioning
confidence: 79%
“…According to Japanese studies, the incidence of IgG4-RD is 0.28-1.08/100,000, and that of IgG4-related ophthalmic disease (IgG4-ROD) accounts for 4-34% of total IgG4-RD cases [3]. IgG4-ROD mainly involves the lacrimal gland, extraocular muscles and trigeminal nerve; the optic nerve, conjunctiva, sclera, uvea, and choroid are rarely involved [4][5][6][7][8]. Despite the rarity of conjunctival involvement in IgG4-ROD [6][7][8], this paper reports a another very rare case of LC with strong positive expression of IgG4 in histopathological results with only one published case in literature.…”
mentioning
confidence: 99%
“…The most involved sites of IgG4-ROD were well established, including lacrimal glands, extra-ocular muscles, orbital soft tissue, and infraorbital nerves [ 12 ]. There were few reports of IgG4-ROD suspected in the isolated lesions of the eyelid and conjunctiva [ 9 , 13 , 14 , 15 ]. Nevertheless, there was no previous report of IgG4-ROD speculated in sweat gland cysts or lesions of other folliculosebaceous unit origins like ours.…”
Section: Discussionmentioning
confidence: 99%
“…It is well-established that IgG4 can be involved in more than one-third of idiopathic inflammation of orbital tissue. It has been shown that higher systemic manifestations of IgG4-RD can be observed in impaired adnexal involvement [11]. These can include changes in immunological and biochemical parameters.…”
Section: Clinical Observationsmentioning
confidence: 99%
“…Additional IgG4-RDs have been identified, based on systemic fibroinflammatory disease characterized by the presence of lesions with lymphoplasmacytic infiltrate with high levels of IgG4-positive plasma cells. In addition,a correlation between higher levels of IgG4 and good response to therapy with corticoids has been observed [2,[6][7][8][9][11][12][13][14][15][16][17][18]. Hamano et al, [19,20] observed not only elevated levels of IgG4 in autoimmune pancreatitis, but also found characteristic histopathological manifestations accompanying retroperitoneal fibrosis.…”
Section: Introductionmentioning
confidence: 99%